Shallow water sea slugs (Gastropoda: Heterobranchia) from the northwestern coast of the Sea of Japan, north of Peter the Great Bay, Russia - Chichvarkhin,Anton (PeerJ, 2016)
The coast of northern Primorye region, north of Peter the Great Bay has been sparsely studied in regards to its molluscan fauna, with just a few works reviewing the distribution of local mollusks. This work presents a survey of the shallow water heterobranch sea slugs currently occurring around Kievka Bay to Oprichnik Bay, Russia. Thirty-nine species of sea slugs were found in this study and the new species Cadlina olgae sp. nov., described herein. Most (24) of the species occurring in the area have widespread ranges in the northern Pacific Ocean. The eight species are endemic for the Sea of Japan and adjacent part of the Sea of Okhotsk. Seven other occur also in northern Atlantic and Arctic waters. Thirteen found species are not known from Peter the Great Bay but known from adjacent northern Pacific waters. The finding of a previously undescribed species emphasizes the need of further surveys, particularly in subtidal and deeper waters, in order to improve the knowledge on this neglected fauna in Primorye.
Keywords: Opisthobranchia; Sacoglossa; Thecosomata; Fauna; Nudibranchia; Cadlina olgae; Cephalaspidea; Sea of Japan; Biogeography